2022
DOI: 10.3390/biomedicines10102481
|View full text |Cite
|
Sign up to set email alerts
|

Oligoprogression of Solid Tumors on Immune Checkpoint Inhibitors: The Impact of Local Ablative Radiation Therapy

Abstract: The breakthrough of a limited number of clones while on immune checkpoint inhibitors (ICIs), known as oligoprogression, has been previously described. The benefit of ablative radiation therapy (RT) directed at these clones, as opposed to changing systemic therapy, is unclear. We analyzed 30 patients with advanced solid tumors, the majority of whom (23/30, 86.7%) had either hepatocellular or urothelial carcinoma, who experienced oligoprogression on ICIs and were referred for RT. In this study, oligoprogression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Although systemic therapy treatments varied after the procedure, most patients had a total immune checkpoint therapy length between 6 and 12 months. Our results are similar to published data demonstrating that time to oligoprogression is not a significant predictor of progression-free survival after local therapy, 25 suggesting that procedural interventions may benefit even patients with biologically more aggressive disease.…”
Section: Original Researchsupporting
confidence: 90%
See 1 more Smart Citation
“…Although systemic therapy treatments varied after the procedure, most patients had a total immune checkpoint therapy length between 6 and 12 months. Our results are similar to published data demonstrating that time to oligoprogression is not a significant predictor of progression-free survival after local therapy, 25 suggesting that procedural interventions may benefit even patients with biologically more aggressive disease.…”
Section: Original Researchsupporting
confidence: 90%
“…12 In a separate study of oligoprogressive lesions in a heterogeneous cohort of solid tumors treated with immune checkpoint blockade, ablative radiation therapy was found to be feasible and resulted in a median progression-free survival of 7.1 months and a 1-year overall survival rate >96%. 25 Most patients in the study continued immune checkpoint therapy after radiation therapy, and at second Original research progression, 15 of 17 patients did so at three or fewer metastatic sites and could have benefitted from additional salvage radiation therapy to further extend the lifespan of immune checkpoint blockade treatment.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 96%
“…In a study conducted by Xu Q et al ( Spry et al, 2018 ), the addition of local ablation therapy to EGFR-TKI demonstrated a satisfactory survival benefit for patients with EGFR-mutated NSCLC who experienced oligoprogression during their first-line EGFR-TKI therapy ( Jiang et al, 2019 ). Similarly, radiotherapy has the potential to improve progression-free survival (PFS) and prolong the efficacy of immune checkpoint inhibitors in patients experiencing oligoprogression ( Sindhu et al, 2022 ). Similar to our findings, these studies indicate that in certain scenarios, patients with advanced disease may still respond well to their previous treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Sindhu et al analyzed 16 patients with HCC who received stereotactic body radiation therapy (SBRT) after oligoprogression during ICI therapy. 14 PFS after SBRT was 7.1 months, with 1year OS was 96.3%. There's an ongoing phase II study of sintilimab plus bevacizumab combined with radiotherapy as first-line treatment for HCC having malignant portal vein thrombi.…”
Section: Radiation Therapy After Ate/bev Failurementioning
confidence: 94%